Ilustración de cubierta, Francisca Pageo - Pageo, Francisca (Asparkía. Investigació feminista, 2024)
<strong style="color: #555555; font-family: 'times new roman'; font-size: 12px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">FRANCISCA PAGEO<span style="color: #555555; font-family: 'times new roman'; font-size: 12px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> (Spain, 1983) <div style="color: #555555; font-family: 'times new roman'; font-size: 12px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; text-align: justify;">Visual artist.Writter. Co-editor & art director of Détour cultura. I've given creative workshops around photography/collage at Distrito Artístico, Fnac-Murcia, CAMON, San Solorea Art Residence, Liv'in The Room, Ilustra-Sevilla & Horno de Luz & I've also given lectures & talks about creativity & visual culture at SOS 4.8 Festival (2012) & Festival Inspira (2013)